Immunogenicity and Safety of a 13-Valent Pneumococcal Conjugate Vaccine Given With DTaP Vaccine in Healthy Infants in Japan. Issue 10 (October 2015) - Togashi, Takehiro; Okada, Kenji; Yamaji, Masako; Thompson, Allison; Gurtman, Alejandra; Cutler, Mark; Aizawa, Masakazu; Gruber, William C.; Scott, Daniel A.
Abstract : Background: 13-Valent pneumococcal conjugate vaccine (PCV13) provides broader protection against pneumococcal disease than 7-valent pneumococcal conjugate vaccine (PCV7). This study performed in Japan compared the safety and immunogenicity of PCV13 with PCV7. Methods: Healthy Japanese infants received PCV13 and diphtheria, tetanus and acellular pertussis vaccine (DTaP), PCV7 and DTaP or DTaP alone subcutaneously as a 3-dose infant series, with a fourth dose at 12 months of age. Antigen-specific immunoglobulin G (IgG) serum concentrations and opsonophagocytic activity and DTaP antibodies were measured 1 month after doses 3 and 4. Results: After 3 and 4 doses, the proportion of subjects in the PCV13 + DTaP group achieving IgG concentrations ≥0.35 μg/mL to the 7 serotypes common to PCV13 and PCV7 was noninferior to that of the PCV7 + DTaP group. IgG geometric mean concentrations (GMCs) in the PCV13 + DTaP group were lower than but noninferior to the PCV7 + DTaP group GMCs. For the 6 additional pneumococcal serotypes, the proportion of PCV13 + DTaP group responders achieving IgG concentrations ≥0.35 μg/mL and IgG GMCs (except serotype 3 after dose 4) was noninferior to the lowest PCV7 + DTaP group pneumococcal response in PCV7 recipients, and responses to the 6 additional antigens were significantly higher. The majority of the subjects achieved prespecified antibody levels to DTaP antigens. GMCs to DTaP antigens were comparable among groups, except filamentous hemagglutinin (numerically higher in the DTaP alone group after dose 4). Conclusions: PCV13 + DTaP was as immunogenic as PCV7 for the 7 common pneumococcal antigens and elicited significantly higher responses to the 6 additional antigens. DTaP responses were comparable across groups. PCV13 given with DTaP was safe and well tolerated.